Influences on Media Content: Levels of Analysis in Developed and Developing Countries - Al-Hasani, Abdulmonam (Bodhi: An Interdisciplinary Journal, 2010)
The aim of this paper is to analyse and discuss theoretical frameworks that relate to influences on media content. This is to identify the suitable models or approaches for studying the influences on media content at news organisations. To achieve this aim, the paper will include two main sections: the first section uses a macro-sociological perspective and will discuss two main theoretical approaches, the political economy and cultural approaches. The second section looks at issues on a micro-sociological level, using the social organisation approach to analyse the definitions of news, news values, gatekeeping and the influences on media content that are internal to news organisations. DOI: 10.3126/bodhi.v2i1.2868 Bodhi Vol.2(1) 2008 p.148-175